Vitrification of mouse embryos at 2-cell, 4-cell and 8-cell stages by cryotop method - Zhang, Junqiang (Springer US, 2009)
PURPOSE: The objective of this study was to investigate the effects of vitrification on the preimplantation developmental competence of mouse 2-cell, 4-cell and 8-cell stage embryos. METHODS: Mouse 2-cell, 4-cell and 8-cell stage embryos were cryopreserved using the cryotop vitrification method and subsequently warmed on a later date. The embryos were then assessed by their morphology, blastocyst formation and hatching rates. Additionally, trophectoderm (TE) and inner cell mass (ICM) cell numbers were compared in hatched blastocysts from the control and experimental groups. RESULTS: Vitrified embryos at the 2-cell, 4-cell and 8-cell stages appeared morphologically normal after warming. The overall survival rate of vitrified embryos at various stages after warming was 96.7% and there were no significant differences among 2-cell stage (96.0%), 4-cell stage (96.8%) and 8-cell stage (97.1%) embryos (P > 0.05). The blastocyst formation rate (69.4%) and hatching rate (52.6%) of vitrified 2-cell embryos were significantly lower than that from the control group and vitrified 8-cell embryos (P < 0.05). In the vitrified 4-cell embryo group, the blastocyst formation rate (90.3%) was similar to the 8-cell group (91.2%), but the hatching rate (60.0%) was significantly lower than that of the non-vitrified control ( 84.1%) and vitrified 8-cell embryo (78.4%) groups (P < 0.05). When further development to the fully hatched blastocyst stage was compared, hatched blastocysts derived from vitrified 2-cell, 4-cell and 8-cell embryos had significantly lower cell counts both in the ICM and TE, as compared to fresh blastocysts (P < 0.05). Among the vitrified 2-cell, 4-cell and 8-cell embryo groups, there were no significant differences in the cell counts of ICM and TE (P > 0.05). CONCLUSIONS: Although cryotop vitrification was suitable for the cryopreservation of mouse embryos from the 2-cell stage, 4-cell stage and 8-cell stage without significant loss of survival, vitrification had an adverse effect on the development of 2-cell embryos. Mouse embryos at the 8-cell stage had the best tolerance for vitrification and would yield the highest level of post-vitrification developmental competence among early cleavage stage embryos. Nevertheless, it is unclear how these findings can be extrapolated to human embryos.